TEORIA E PRÁTICA DOS GÊNEROS JORNALÍSTICOS: estudo empírico dos principais diários das cinco macro-regiões brasileiras - Costa, Lailton Alves da (2008)
This research identifies the journalistic genres used in the contemporary brazilian press, through a comparison e analysis of texts published in the five most important newspapers of each geographical regions of Brazil in relation to theoretical studies developed in the academy. We selected for the analysis seven issues of each newspapers published in the monthes of november and december of 2006. As methodology, we adapted the Content Analysis as it is used in the Communication Sciences and in Language Sciences, according to the theories of the scholar Marques de Melo. The data analyses revealed that the genres Informative and Opinion Related, that are very common in the practical life of the brazilian journalists, matches the genres as they are appointed by the academic theories. The study also demonstrates the genre Utilitarian is legitimated by the journalist practical life as it is by the academy world. The Interpretative Related genre showed irrelevant presence in the pages of the newspapers while the Diversions Related genre as not found at all. The analyses concluded that there has been no important creation of new genres in the brazilians newspapers in the last few years.(AU)